Association of weight-adjusted waist index with preserved ratio impaired spirometry and all-cause mortality - Jiao, Xin; Huang, Linqi; Lin, Luoqi; Zhu, Fanggang; Fan, Feiting; Xiao, Jingmin; Wu, Lei; Lin, Lin; Chen, Yuanbin (Frontiers in Nutrition, 2025)
BackgroundPreserved ratio impaired spirometry (PRISm) is considered an early indicator of chronic obstructive pulmonary disease (COPD). This study aimed to investigate the association between weight-adjusted waist index (WWI) and PRISm, and the impact of WWI on all-cause mortality in U.S. adults with and without PRISm.MethodsThis combined cross-sectional and cohort study analyzed data from 9,841 participants in the 2007–2012 National Health and Nutrition Examination Survey (NHANES). Weighted logistic regression assessed the association between WWI and PRISm. Kaplan–Meier survival curves and weighted Cox regression evaluated the effect of WWI on all-cause mortality. Restricted cubic spline (RCS) analysis explored both linear and nonlinear relationships between WWI and outcomes.ResultsAfter covariate adjustment, each unit increase in WWI was associated with a 45% reduced risk of PRISm (ORs = 0.55; 95% CIs: 0.47–0.65). RCS analysis revealed a nonlinear WWI-PRISm relationship (p for nonlinearity = 0.0012). In the PRISm population, each WWI unit increase associated with an 88% higher adjusted all-cause mortality risk (HRs = 1.88; 95% CIs: 1.38–2.56). A U-shaped curve characterized the nonlinear WWI-mortality association in PRISm (p for nonlinearity = 0.0025), whereas positive linear trends were observed in non-PRISm individuals and overall.ConclusionLower WWI levels were linked to an elevated PRISm risk, highlighting central obesity’s role in respiratory health. Maintaining an optimal WWI may mitigate mortality risk in adults with PRISm, emphasizing the need for targeted weight management.